Measuring Attitudes Towards Motorcycle Helmet Use in Laos - Sim-Sim, Margarida (2020)
This paper examines attitude towards use of motorcycle helmet in Laos. A quantitative approach using the survey questionnaire method was adopted to assess this attitude. A total of 257 university students in Vientiane, Laos was interviewed. Forward translation, backward translation, and cognitive debriefing were carried out. Factor analysis of the principal components was also performed. The four-factor solution was used to explain the 58.867% of total variance. The correlation between items showed values between .01 and .566. The total item correlation values were between .129 and .566. Cronbach alpha coefficient was .764 for overall scale and between .801 and .601 on the four factors. Spearman Brown prediction formula was used to test psychometric properties and reliability of the items. A total of 17 items were considered reliable, such as such as susceptibility, trafficability, safety and usability, in determining overall attitudes of Laotians in using motorcycle helmet. These can be used in future research.